INTERSECTIONAL ENVIRONMENTALISM: Toward an Indigenous Peoples-Inspired Planetary Ethics - Biana, Hazel; Rivas, Virgilio (Journal of Dharma, 2021)
“Indigenous Peoples” (IPs) are specifically mentioned in the 2030 Agenda for Sustainable Development. The SDGs advocate the empowerment, education, and engagement of IPs in the agenda’s implementation, one of which is protecting the planet’s natural resources and re-establishing a stable climate for next generations. UN Indicators suggest that IPs’ experiences and rights are unique. IPs, however, criticize these indicators as unreflective of ‘Indigenous definitions of well-being’. Intersectional environmentalists assert the same that various groups relate to the planet differently. We look at the IP agenda through the lens of intersectional environmentalism and its underlying ethics of trans-corporeality, broadly reflecting an ecofeminist disposition. With 85% of the Philippines’ key biodiversity areas located within ancestral domains, the country’s IPs’ struggles exemplify a more balanced and sensitive approach to planetary sustainability, thus the need to support and expand IPs’ planetary ethics.